Реформування оплати праці в бюджетній сфері: досвід окремих країн СНД та висновки для України - Новак, І.М. (Інститут демографії та соціальних досліджень НАН України, 2007)
The article is devoted to the analysis of a modern situation in Ukraine and experience of the separate CIS countries concerning reforming a payment of workers of budgetary sphere. The most important conclusions on adaptation of the analysed foreign experience and its use for providing of formation of national policy in the emphasized sphere were made.